Inclusive Economic Development Model as the Alternative of Sustainable Social-Economy Engineering -a Case of Tourism-Based Social Economy Development in Wakatobi Regency (European Journal of Marketing and Economics, 2024)
Basically, inclusive economy development is the economy development contributing to majority of people in Indonesia aiming to poverty reduction.  In the situation where the challenges become more complicated, the tourism development could be directed to the inclusive economy development based on tourism.  It supports tourism growth centers.  This enables to get inequality income and poverty reduction through pro poor tourism. This research uses an action research through observation toward various aspects relating to the development of inclusive economy.  The results of this research identify that integrated tour and travel businesses become prospective business; furthermore, handy craft, food and beverages industries.   If it is related to SWOT Analysis and study of tourism market; also the perception of local people, the most crucial consideration in developing the tourism based inclusive economy in Wakatobi is a forming of synergy among the large businessmen and people business as well as all people supports.  Therefore, all tourists visiting Wakatobi get pleasure and satisfied and the businessmen get more and better benefits and profit.  Another result shows that action to synergize businessmen is required to vague conflicts causing and occurring unhealthy competition.  The creating of among-businessmen synergy is derived to be business model of tourism based associate-businessmen in Wakatobi Regency.   The early step of the development of tourism based inclusive economy is conducted well, however there are some constrains to be considered to maintain and develop the formulated model and for that, risk assessment could be used.
Keywords: inclusive economy, sustainable development, business model and social-economy development